Phytochemical Content of Tingi (Ceriops tagal) Bark Extract by Ultrasonication Process - Guring Briegel Mandegani; Rini Pujiarti; Ganis Lukmandaru (Faculty of Forestry Universitas Gadjah Mada, 2024)
Tingi (Ceriops tagal) becomes one of the natural dyes used in textile dyeing. Ultrasonication is an extraction method that requires less time than conventional methods. Therefore, this study aimed to determine the effect of the ultrasonication duration (20, 40, 60, 80, and 100 minutes) on the total phenolic content (TPC), total flavonoid content (TFC), and total tannin content (TTC). The extraction yield was calculated by drying the solution with a freezer dryer, and phytochemical content was determined using UV-vis spectrophotometry. The results indicated that the yield value of the duration treatment was in the range of 3.74% to 5.53%, which was lower than the conventional method (10.58%). However, TPC, TFC, and TTC had more optimal values than the conventional method, with TPC values ranging from 268.1 to 314.1 mgGAE/g sample, TFC ranging from 68.3 to 87.1 mgQE/g sample, and TTC ranging from 244.8 to 338.1 mgTAE/g sample. The highest compound content was observed at 20 minutes, indicating that the ultrasonication method can be applied to extract Tingi bark as natural dyes.